Widespread freshening in the Seasonal Ice Zone near 140°E off the Adélie Land Coast, Antarctica, from 1994 to 2012. Issue 11 (13th November 2013) - Aoki, S.; Kitade, Y.; Shimada, K.; Ohshima, K. I.; Tamura, T.; Bajish, C. C.; Moteki, M.; Rintoul, S. R.
<x xml:space="preserve">Abstract</x> [1] Long‐term water mass changes during 1994–2012 are examined from nine repeat hydrographic sections in the Seasonal Ice Zone along 140°E, off Antarctica. Significant freshening trends are detected within most of the water masses from the bottom to surface. Bottom Water freshened by 0.008–0.009 decade−1 below isopycnal surfaces and its layer thickness decreased by 120–160 dbar decade−1 throughout the study period. In addition to general thinning, the layer thickness was anomalously thin in 2012, suggesting a possible link with the sudden calving of the Mertz Glacier Tongue and subsequent reduction in sea‐ice production. Winter Water freshened by 0.03 decade−1 throughout the study period, with significant interannual variability. In the offshore region, a long‐term increase in precipitation can explain a substantial portion of the freshening trend. The Lower Circumpolar Deep Water on the continental slope underwent freshening at the same rate as the Bottom Water during the last two decades. Modified Shelf Water also shows robust freshening at a rate of 0.03 decade−1. Combined with the freshening of near‐surface and Bottom Water masses in this region, these data indicate freshening of the entire water column over the continental slope. This widespread freshening is broadly consistent with the enhancement of the global hydrological cycle, together with a possible acceleration of land ice melting.